Hydrological and Hydraulic Modelling of Sekolo River Diversion for Coal Mining Activities - Wahyu Gendam Prakoso; Dinta Anindy Ismiralda (Civilla : Jurnal Teknik Sipil Universitas Islam Lamongan, 2024)
A Hydrological and hydraulic modeling of the proposed diversion of the Sekolo River for coal mining purposes will provide an overview and technical information on the proposed river realignment and identify potential impacts on the use of the Sekolo River. It is being carried out for River extension to maintain river sustainability and functionality. Sekolo River watershed modeling utilizes a combination of hydrological analysis and open-channel hydraulic modeling using HEC-HMS and HEC-RAS software. To meet the area criterion (volume), the dimensions of the diversion channel are planned with B = 15 m.  H = 1.5 m; m = 1.5; L = 1253 m. These dimensions make the volume of the diversion approximately the same as the existing river. Hydraulic simulation results showed that the flood level would not rise downstream of the diversion channel. The upstream (Q25) peak flow rate is 41.90 m3/s, while the downstream peak flow rate after diversion is increased by 0.02% compared to the existing flow rate. After introducing the diversion channel, the difference in flood peak arrival time (Tp) will be 3 minutes earlier than before the diversion.